Experiences of Interactions within Parental Couples of Children with Sickle Cell Disease: The Case of Four Cameroonian Couples - Hassan Njifon Nsangou; Adrien Hervé Dountio Takou; Martial Nguegno Fouadjo (Nusantara Journal of Behavioral and Social Science, 2026)
Sickle cell disease (SCD) is a chronic and potentially life-threatening genetic disorder that affects approximately 5% of the global population, with particularly high prevalence rates in sub-Saharan Africa and in Cameroon, where it reaches 8.34%. Beyond its medical complications (such as recurrent pain crises, anemia, and frequent hospitalizations) SCD has profound psychosocial consequences that extend to the entire family system. In particular, it reshapes parental roles, responsibilities, and emotional experiences within couples. This study aimed to explore how parental dyads in Cameroon interact while caring for a child with SCD, with specific attention to communication patterns, emotional experiences (anger, distress, support), and negotiation of caregiving responsibilities. A qualitative design was employed, involving semi-structured interviews with four couples. Data were analyzed using inductive thematic content analysis. The findings reveal that functional communication, shared decision-making, and mutual emotional support strengthen parental coping and cohesion. Conversely, limited dialogue, unequal caregiving involvement, and lack of emotional reciprocity contribute to heightened stress and psychological distress, particularly among mothers. These results highlight the importance of considering the couple as a relational unit in pediatric chronic illness management. Clinical implications suggest that interventions focused on enhancing couple communication, promoting equitable caregiving roles, and strengthening dyadic support may improve both parental well-being and child health outcomes.